WHAT MOTIVATES RESIDENTS’ RECYCLING BEHAVIOUR IN DIFFERENT AREAS? A STUDY OF RESIDENTS IN CITY AND SEMI DENSE AREAS IN JOHOR - Muhammad Majid; Mohamad Faizal Ramli; Ahmad Syahmi Ahmad Fadzil; Nur Fatihah Shaari; Basri Badyalina; Mohd Danial Afiq Khamar Tazilah, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
All residents must receive recycling education because environmentally conscious residents are more likely to become environmentally conscious citizens. In addition, recycling is known to be one of the strategies used to reduce reliance on landfills; this is important because further inaction will lead to landfills reaching maximum capacity. The study intends to explore the factors affecting the recycling behaviour among residents in the city and semi-dense areas in Johor, Malaysia. In this study, 400 respondents who live in highly dense areas (city) and semi-dense areas in Johor, Malaysia, will be surveyed. Multistage sampling will be utilised to choose the sample (recycling and non-recycling residents), and a questionnaire with closed-ended questions will be developed to gather study data. Regression, correlation, and descriptive statistics will examine the acquired data. These findings are expected to offer policymakers like district offices, municipal councils, city councils, and non-government organizations (NGOs) helpful information to plan and develop a more effective recycling policy and activities in Malaysia.